Evaluation of Climate Resilient Groundnut Genotypes for Thermo Tolerance under Climate Change - John, K.; Santhoshi, M. V. Madhavi; Rajasekhar, P. (International Journal of Bio-resource and Stress Management, 2019)
A total of about one hundred groundnut (Arachis hypogaea L.) genotypes were evaluated for temperature tolerance. The per se performance under induced temperature, the mean root length ranged from 0.00 (ICGV-05155, ICGV-06424, ICGV-07247 and ICGV-07273) to 6.90 cm (TCGS-1837). The mean shoot length ranged from 0.00 (TCGS-1826, ICGV-05155, ICGV-06423, ICGV-06424, ICGV-07222, ICGV-07225, ICGV-07240, ICGV-07245, ICGV-07247, ICGV-07262, ICGV-07235, ICGV-07273, ICGV-07395, ICGV-07337, ICGV-07406, MLTG-03, MLTG-09, MLTG-11andNarayani) to 3.20cm (TCGS-1522). Under lethal temperature, the mean root length ranged from 0.00 (ICGV-05155, ICGV-06424, ICGV-07247 and ICGV-07273 to 6.9 cm (TCGS-1837). The mean shoot length ranged from 0.00 (TCGS-1826, TCGS-1843, TCGS-1859, TCGS-1861, ICGV-06423, ICGV-06424, ICGV-07219, ICGV-07220, ICGV-07222, ICGV-07225, ICGV-07228, ICGV-07240, ICGV-07241, ICGV-07245, ICGV-07247, ICGV-07268, ICGV-07235, ICGV-07270, ICGV-07273, ICGV-07286, ICGV-07390, ICGV-07392, ICGV-07395, ICGV-07396, ICGV-07296, ICGV-07337, ICGV-07403, ICGV-07404, ICGV-07405, ICGV-07406, ICGV-7408, MLTG-02, MLTG-03, MLTG-04, MLTG-06, MLTG-08, MLTG-09, MLTG-11, Narayani and K-6 to 3.00 cm (TCGS-1522 and TCGS-1824). The best performing groundnut genotypes viz.,TCGS-1508, TCGS-1511, TCGS-1514, TCGS-1516, TCGS-1517, TCGS-1520, TCGS-1521, TCGS-1522, TCGS-1523, TCGS-1527, TCGS-1529, TCGS-1804, TCGS-1807, TCGS-1809, TCGS-1810, TCGS-1813, TCGS-1814, TCGS-1815, TCGS-1817, TCGS-1818, TCGS-1819, TCGS-1820, TCGS-1821, TCGS-1822, TCGS-1824, TCGS-1825, TCGS-1829, TCGS-1831,TCGS-1837, TCGS-1838, TCGS-1839, TCGS-1845, TCGS-1851, TCGS-1853, TCGS-1855, TCGS-1868, TCGS-1869, TCGS-1872, TCGS-1876 and ICGV-07262 were found promising climate resilient groundnut genotypes based on survival under lethal temperature.Some of the genotypes showed better performance under induced and lethal temperatures for root and shoot lengths such as TCGS-1511, TCGS-1520, TCGS-1521, TCGS-1522, TCGS-1528, TCGS-1529, TCGS-1804, TCGS-1807, TCGS-1809 and TCGS-1810.These promising genotypes could be utilized in the breeding programme as donors to develop high yielding drought tolerant genotypes.